2022
DOI: 10.1038/s41598-022-23460-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient ultra-broad beam silicon nanophotonic antenna based on near-field phase engineering

Abstract: Optical antennas are a fundamental element in optical phased arrays (OPA) and free-space optical interconnects. An outstanding challenge in optical antenna design lies in achieving high radiation efficiency, ultra-compact footprint and broad radiation angle simultaneously, as required for dense 2D OPAs with a broad steering range. Here, we demonstrate a fundamentally new concept of a nanophotonic antenna based on near-field phase-engineering. By introducing a specific near-field phase factor in the Fraunhofer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Surface gratings as optical antennas are designed to radiate the light out of the chip, facilitating free-space beam shaping and steering, which is desired for surging applications in LIDARs or free-space optical communications. Both very long (mm-scaled) andultra-short (μm-scaled) surface gratings with weak and strong radiation can be advantageously utilized as efficient optical antennas in one-dimensional (1-D) or two-dimensional (2-D) OPAs [35][36][37][38]. Figure 2a show a schematic view the optical nano-antenna implemented on a 220 nm thick SOI platform.…”
Section: Silicon Antennasmentioning
confidence: 99%
“…Surface gratings as optical antennas are designed to radiate the light out of the chip, facilitating free-space beam shaping and steering, which is desired for surging applications in LIDARs or free-space optical communications. Both very long (mm-scaled) andultra-short (μm-scaled) surface gratings with weak and strong radiation can be advantageously utilized as efficient optical antennas in one-dimensional (1-D) or two-dimensional (2-D) OPAs [35][36][37][38]. Figure 2a show a schematic view the optical nano-antenna implemented on a 220 nm thick SOI platform.…”
Section: Silicon Antennasmentioning
confidence: 99%
“…The results showed that the unidirectional transmission efficiency of the grating antenna increased from 46% to 95% after the DBR were added. Shahrzad Khajavi et al achieved an emission efficiency of 82% while designing a nanophotonic antenna based on near-field phase engineering, by incorporating a bottom Bragg reflector into the structure [35], but this structure in the process of production is more complicated.…”
Section: The Directivity Of Diffractionmentioning
confidence: 99%
“…Earlier works on silicon (Si) [1][2][3][4][5][6] stimulated the progress in numerous Si-photonics devices, including vertical-cavity surfaceemitting lasers (VCSELs), [7] distributed feedback (DFB) lasers [8] and efficient nanophotonic antennas, [9] supercontinuum generation, [10] and optoacoustic detection. [11] Within these photonic devices, Bragg gratings (BGs) are critical and used to improve the efficiency of the devices.…”
Section: Introductionmentioning
confidence: 99%